Alternative way to find sacral hiatus for blind caudal block – Based on 3D pelvis CT anthropometry: A retrospective study. (December 2018) - Oh, Saechol; Chung, Kyudon; Bang, Seunguk; Kim, Seo Yeong; Kwon, Woojin
Abstract: The aim of this study is to develop an alternative way to locate the sacral hiatus for blind caudal block from the anthropometrical data measured on 3D pelvic CT. The intersection of the line connecting two sacral cornua and the midline is considered the ideal point (IP) for caudal block. The mean length from the coccyx tip to the IP was measured using 3D pelvic CT images in 30 men and 30 women and was 6.5 cm and 6.0 cm, respectively. For the conventional method group, we used the conventional equilateral triangle method to find the sacral hiatus, which was named conventional method group needling point (CNP). For the experimental method group, the point 6.5 cm or 6.0 cm (mean length from the coccyx tip to the IP) away from the coccyx tip was called the experimental method group needling point (ENP). Drawing the three points of the IP, CNP, and ENP on the same patient's 3D pelvic CT, we compared the distance from the IP to the CNP with the distance from the IP to the ENP. We propose that the experimental method is comparable to the conventional method in locating the sacral hiatus, which is crucial for a successful caudal block procedure. Anthropometric measurements and virtual comparative test between two methods were done on the 3D pelvis CT. In men, the distance from the CNP to the IP was 0.8 ± 0.5 cm in the conventional method group, while the distance from the ENP to the IP was 0.5 ± 0.4 cm in the experimental method group (p < 0.05). In women, the same distances were 1.5 ± 0.8 cm and 0.7 ± 0.3 cm, respectively (p < 0.05). In conclusion, finding a point of 6.5 cm from the coccyx tip in men and 6.0 cm in women could be an alternative way to find the sacral hiatus for blind caudal block.